Animal Depictions in Philistia and Judah during the Iron Age - Ben-Shlomo , David (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2024)
The more common iconographic representations of animals in Iron Age Philistia and Judah will be discussed and compared in this paper. These representations include terracottas, decoration on pottery, ivories seals and sealings and other media. Certain regional differences can be detected easily, both in terms of style and symbolism. In particular, the style of the figurines from Judah is more schematic and the main theme is the horse, while in Philistia bovines and birds are more popular. The bovine is a well-known and popular motif in the Canaanite, Egyptian and Aegean cultures, while the popularity of birds seems to be a Philistine innovation. During the Iron Age II the Philistine animal depictions are still rich and relatively diversified while in Judah they are largely limited to horse and rider figurines and glyptics. The paper will discuss and compare the possible significances of animal representations in Philistia and Judah.